Decentralizáció és regionalitás a horvát uniós csatlakozás árnyékában - Lőrinczné Bencze, Edit (Közép-Európai Közlemények, 2013)
The paper presents the basic issues of regional and cohesion policy in Croatia with an emphasis on general administrative reforms and decentralization process as well as the effects of Croatian accession to regional policy. One of the main characteristics features of Croatia’s regional policy is extreme fragmentation of territorial and administrative units and huge the spatial inequalities. On the bases above it seems that in the modern approach to regional development shaped through the aid to undeveloped and war affected lagging areas, without a strategic mechanisms resulted in a number of deficiencies and it was just in December 2009, when the Law on Regional Development was passed and in summer 2010 year when Strategy was adopted. On the other hand process of accession of Croatia to the European Union also bears important effects for regional development, such as the obligation the defining of wider regions, i.e., after a long debate introducing two statistical planning regions at NUTS 2 level in Croatia, which represent a territorial level at which Cohesion policy is mainly implemented or preparing the necessary national institutional framework in order to meet the EU accession criteria and to access the structural and cohesion funds, after having obtained the member state status.